A macroscopic traffic flow model considering driver memory effect on curves - Yang Chunfeng; Yang Chenxiao; Zhang Yu; Qi Linyuan; Shi Longyu; Tan Lixiang; Tang Qiang (Results in Physics)
In real-world driving environments, curved roads are a common scenario that drivers must consider. Driver behavior is also a key factor in the study of traffic systems. This study investigates how factors such as curvature radius and friction coefficient affect the stability of a memory-dependent vehicle-following model under curved road conditions. First, stability criteria for the model are derived using control theory. Subsequently, equilibrium solutions are obtained through bifurcation analysis from a nonlinear perspective. Numerical simulations demonstrate that the model effectively captures system dynamics on curved roads. The incorporation of driver memory effects adversely impacts system stability, and similar destabilizing trends emerge with increasing curvature radius and friction coefficient. Furthermore, numerical solutions exhibit strong consistency with analytical results.